An exploratory Investigation of Virtual Worlds: Proposed Business Models in Second Life - Chiu, Kung-chak (2008)
With the growing awareness on the research of virtual worlds, it is claimed the development of virtual world is not merely the gaming purpose but which is rife with moneymaking opportunities. To further interpret the feasibilities of the models, scholar and practitioners have investigated and analyzed the literature of business model from various perspectives and theories. In this dissertation, Second Life (SL) is selected as the most appropriate platform for demonstrating the proper adoption of business model and application in virtual worlds. Based on the research on virtual worlds and relevant literature, the business models and applications in SL can be classified as Virtualization of Real Products; New Virtual Products or Services and Physicalization of Virtual Products or Services. In the light of research on virtual worlds, the major characteristics of VW embrace Interactivity, Immersion and Network Effects. After investigating the Media Richness Theory and Task Closure Theory, some elements generalized from these theories form some theoretical-based indicators to evaluate the 99 selected companies in Second Life. These theories suggest several significant factors which include Feedback Capability, Intuitive Cues, Avoid Overburdened Non-intuitive Cues, Personal Focus, Task Closure, Virtual Availability and Social Presence.